Vulnerability of Teenagers to sects' recruitment - Mª Ángeles Hernández Prados; David Ibáñez Bordallo (Pontificia Universidad Católica del Perú, 2017)
The uniqueness» fracture of the ruling speech about modernity has plunged us into despair of relativity voices of postmodernism. We assist, according to Garcia (2008), to a new era characterized by the implementation of a spiritual market and a religions cocktail. The increased sensitivity of citizenship by cultivating integrity along with the host institutions crisis exacerbates the vulnerability of people to be influenced of sectarian ideologies. After having analyzed society as a beneficial crop to the sects, the speech focused on adolescence as the most vulnerable stage, claiming that education, from many different contexts, is the most likely response to prevent the sect»s recruitment.